Lymphoepithelioma like Carcinoma of the Bladder - "A Case" Revisited - Mezhuneituo Raleng; Gaurav Aggarwal; Sujoy Gupta (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2020)
Lymphoepitheliomas are a type of undifferentiated carcinomas primarily described in the nasopharyngeal cavity. In the urinary tract, they are typically, but uncommonly seen in the urinary bladder, although occasional cases have been reported in the renal pelvis, ureter and urethra. Lymphoepithelioma-like carcinoma of the urinary bladder, first reported by Zuckerberg, et al. in 1991, is uncommon with a reported incidence between 0.4 and 1.3% of all bladder carcinomas. We report the case of an 82 year old gentleman, who presented with a bladder mass, which was post surgical intervention, diagnosed to be a Lymphioepitelioma like carcinoma, with an aim to add to the available literature, and help re-visit and establish appropriate treatment strategies.